1995
DOI: 10.1002/ijc.2910600118
|View full text |Cite
|
Sign up to set email alerts
|

Reverse‐zymographic analysis of protease nexin‐II/amyloid β protein precursor of human carcinoma cell lines, with special reference to the grade of differentiation and metastatic phenotype

Abstract: Trypsin inhibitors in serum-free conditioned media (SFCM) of various human carcinoma cell lines were analyzed by reverse zymography. Most of the cells secreted high-molecular-weight trypsin inhibitors (HMTI) larger than 100 kDa. The cell lines of colorectal carcinoma origin had a tendency to secrete HMTI whose molecular weight was a little higher than that of the other cell lines. Analysis of SFCM of subclones with different histological differentiation and metastatic/invasive potentials derived from a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…DISCUSSION An important goal of our study was to determine whether APP production could influence the growth of human colon carcinoma cells in vitro and in vivo, since we have observed that most carcinoma cells express APP and that a major serine proteinase inhibitor secreted by a number of colon carcinoma cell lines is sAPP with Kunitz-type serine proteinase inhibitor domain. [3][4][5] Here, we demonstrated that down-regulation of APP in SW837 human colon carcinoma cells resulted in markedly reduced cellular growth in vitro, and more importantly, also in vivo. The reduced growth in vitro was restored by the addition of a cultured conditioned medium of parent SW837 cells, whereas the conditioned medium pretreated with anti-APP antibody followed by immunoprecipitation failed to restore the antisense effect.…”
Section: Reduced Tumor Growth Of App Antisense Clones In Nude Micementioning
confidence: 70%
See 4 more Smart Citations
“…DISCUSSION An important goal of our study was to determine whether APP production could influence the growth of human colon carcinoma cells in vitro and in vivo, since we have observed that most carcinoma cells express APP and that a major serine proteinase inhibitor secreted by a number of colon carcinoma cell lines is sAPP with Kunitz-type serine proteinase inhibitor domain. [3][4][5] Here, we demonstrated that down-regulation of APP in SW837 human colon carcinoma cells resulted in markedly reduced cellular growth in vitro, and more importantly, also in vivo. The reduced growth in vitro was restored by the addition of a cultured conditioned medium of parent SW837 cells, whereas the conditioned medium pretreated with anti-APP antibody followed by immunoprecipitation failed to restore the antisense effect.…”
Section: Reduced Tumor Growth Of App Antisense Clones In Nude Micementioning
confidence: 70%
“…Although the precise mechanism underlying this finding is undefined, it may be in accordance with our previous observation using cloned sublines derived from a single pancreatic adenocarcinoma cell line. 4 In that study, the levels of sAPP in SFCM of the subclones correlated to the degree of histological differentiation in vivo. Given the possible roles of APP in cell-ECM and cell-cell interactions as mentioned above and the observations that cellular microenvironment such as cell-ECM interaction could play an important role in glandular differentiation of adenocarcinoma cells, 30 suppression of APP may somehow impair the cell-ECM and/or cell-cell interactions that are involved in the formation of tubular structures.…”
Section: Reduced Tumor Growth Of App Antisense Clones In Nude Micementioning
confidence: 84%
See 3 more Smart Citations